Education nursing students' in Palliative Care and Pain Therapy: an observational study - La Sala, Rachele; Cazzato, Serena; Cecchi, Rossana; Marletta, Giuseppe; Martelli, Michele; Coppola, Debora; Cavalli, Lisa (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: University education plays an important role in the preparation of future nurses, especially in the care of dying patients, which is one of the most emotionally engaging aspects. The objectives of the study were to describe the attitudes of students in end-of-life care and to analyze the possible relationship with some socio-demographic variables, through an observational study.Methods: Preliminarily, an analysis of the educational context of the Nursing Course  of the University of Parma was started, through a comparison of the university course with the recommendations of the MIUR concerning the teaching and learning of Palliative Care and Pain Therapy. Subsequently, a questionnaire containing the Frommelt Attitude Toward Care of the Dying Scale Form B and some socio-demographic context variables was administered to a sample of 109 students belonging to the CoS of Nursing in Parma.Results: From the data collected, it emerged that university planning partly reflects the recommendations of the MIUR and how, on average, nursing students have described positive attitudes in all the dimensions investigated. Interesting is the presence of a positive relationship between the personal experiences of bereavement and the attitudes of the students.Conclusions: Nurses are essential in ensuring the quality of care provided to patients at the end of life; Nursing training in Palliative Care and Pain Therapy should include a complete and varied program (frontal activity, simulation, internship paths...) in order to develop positive student attitudes associated with high levels of satisfaction and improvement of the quality of care provided.